KONVERSI BEKAS HAK MILIK ATAS TANAH ADAT DAN PEN DAFTARANNYA DALAM MENUNJANG TERCAPAINYA SISTEM INFORMASI PERTANAHAN DI PROPINSI DAERAH ISTIMEWA YOGYAKARTA - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
This research was a descriptive qualitative research and aimed at finding out factors which impeded the owners ofexcustomary ownership right from converting istrating their right according to the Act No.5 of 1960. Primary data were obtained from respondents and informants whiieses-elfdary data were obtained through library and documentary study. Randomly taken, the respondents were owners of excustomary land right, both with certificate and not, while informants were Provincial Head of National Land Agency District Heads of National Land Agency in each District, namely Sleman, Bantul and Yogyakarta municipality, and Heads of related subdistricts and villages. Result of the research showed that out of 4 respondents, 45 respondents (53,57%) did not have certificate and 39 respondents (46,43%) had certificate. The factors which impeded them from converting and registrating their right were that cost for conversion and registration proses were too high and there were illegal cost components